2010
DOI: 10.1145/1880022.1880029
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Spoken Phrases in Encrypted Voice over IP Conversations

Abstract: Although Voice over IP (VoIP) is rapidly being adopted, its security implications are not yet fully understood. Since VoIP calls may traverse untrusted networks, packets should be encrypted to ensure confidentiality. However, we show that it is possible to identify the phrases spoken within encrypted VoIP calls when the audio is encoded using variable bit rate codecs. To do so, we train a hidden Markov model using only knowledge of the phonetic pronunciations of words, such as those provided by a dictionary, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…For example, in certain circumstances the size of packets from a codec that compresses voice can be used to identify spoken phrases [11]. Such an attack could be applied in a femtocell setup.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in certain circumstances the size of packets from a codec that compresses voice can be used to identify spoken phrases [11]. Such an attack could be applied in a femtocell setup.…”
Section: Discussionmentioning
confidence: 99%
“…This information is particularly sensitive. Other research has shown that the throughput of Voice over Internet Protocol (VoIP) applications can be used to identify the language of speech (Wright, Ballard, Monrose, et al, 2007) and even to detect specific spoken phrases (Wright, Ballard, Coull, et al, 2010), thus allowing a no-permission app to eavesdrop on private phone conversations. This side channel may also allow an app to learn coarse-grain location information by monitoring the throughput of mapping apps as they load map segments as the user moves around.…”
Section: What Private Information Is Accessible By Android Apps That mentioning
confidence: 99%
“…A similar approach has been used to identify specific phrases in encrypted voice over IP (VOIP) traffic [15]. When variable bit rate encoding is used by the VOIP codec, the encodings of different classes of phonemes require predictable ranges of bit sizes; producing a vulnerability similar to the one in [14].…”
Section: Brief Survey Of Side-channel Attacks On Tunneled Protocolsmentioning
confidence: 99%
“…Instead of using standard HMM approaches that require an a priori known state space for training, we require no prior knowledge. Instead of using maximum likelihood metrics [4,5,[15][16][17], we combine HMMs with statistical hypothesis testing which provides a theoretical basis for determining threshold values [28][29][30]. Hypothesis testing allows us to determine the statistical significance of the inferred model, which in turn indicates whether or not the volume of training data is sufficient [28][29][30].…”
Section: Hmm Inferencementioning
confidence: 99%